Global perspectives on green business administration and sustainable supply chain management, 1st ed. - Sánchez Flores, Rebeca; Cruz-Sotelo, Samantha; Ojeda-Benitez, Sara (Hershey, PA: IGI-Global., 2020)
This chapter presents an overview of current research on green practices said to improve global supply chain performance by driving the discussion into four main processes: sourcing, manufacturing, logistics, and customer service. Authors present the importance of sustainable development in supply chain management from environmental and green perspectives. The chapter undertakes a literature review on supply chain management, sustainable performance, and green supply chain. It continues with a discussion of green supply chain practices from different functions' perspectives, as strategic sustainable performance improvement and as a source of competitive advantage for business operations throughout the supply chain. Finally, this chapter identifies research gaps, discusses potential research directions for green supply chain management, and provides recommendations to expand on research to address the shortcomings of the existing literature.
Green practices in supply chain management to improve sustainable performance
Keywords: Sustainable performance; Supply Chain; Campus Mexicali